PENGEMBANGAN PRODUK LUNPIA DENGAN PENAMBAHAN DAGING RAJUNGAN DAN ANALISA KELAYAKANNYA - Muhammad Yusuf (Universitas Muhammadiyah Semarang, 2012)
Research on product development lunpia crab is still potential to be studied and developed further. One of the development effort was tested through the use of swimming crabs (rajungan) became the crab lunpia product. With the new product is expected to further popularize lunpia as traditional foods ofSemarang and also to promote it. Lunpia product development is the result of laboratory-scale trials using raw crab with organoleptic tests has an average value of 6.050. Product that has the highest preference test and became product that is developed with the specification; 0.7 mm skin thickness andcomposition of crab 60% by improving the skin to be 1 mm to improve the appearance of the product. Feasibility analysis indicates that the crab lunpia product development efforts are profitable and feasible to be developed.Keyword : crab, product development, crab lunpia